Self-Management Team Pemeliharaan Perangkat Layanan Telekomunikasi Seluler - Rosimah, Siti (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2020)
The services of cellular telecommunication companies are very complex and should be available any times. To deliver services used equipment that complexity and properly all the times and the system not damage or function of degradation. Therefore, the equipment maintained the network system that properly to function at any time. To maintain the equipment required the autonomous maintenance team in maintenance activities. Self-management team as a teamwork concept approach that explored maintenance activities of equipment telecommunication